#TITLE_ALTERNATIVE# - Rajagukguk (NIM 235 04 016), Henry
Abstract: Distributed database design by Top-Down approach is achieved in two phase of process, i.e. fragmentation and allocation. Fragmentation is a process to devide a relation into subrelations. Those subrelations is called fragments. Fragments produced are then allocated to every site in a distributed database system. There are two basic teqniques of fragmentation, i.e. vertical fragmentation and horizontal fragmentation. Vertical fragmentation is a process to devide a relation into subrelations based on the attribute of a relation. Vertical fragmentation can be achieved using the BVP (Binary Vertical Partitioning) algorithm. Three steps of process must be done if a relation is desired to be fragmented using the BVP algorithm: (1) the process of AAs matrix construction, (2) the process of CAs matrix construction and (3) finds a split point in CA matrix. The process of CAs matrix construction is a process that clusters attributes of a relation based on affinity in AAs matrix. The process of CAs matrix construction of BVP algorithm is an unpractical process. This thesis proposes an alternative method of CAs matrix construction that can be used to cluster attribute (replace step 2 of BVP algorithm).